Antiretroviral therapy adherence patterns, virological suppression, and emergence of drug resistance: A nested case–control study from Uganda and South Africa. Issue 5 (20th October 2022) - Tyagi, Anisha; Tong, Yao; Rabideau, Dustin J; Reynolds, Zahra; De Oliveira, Tulio; Lessells, Richard; Amanyire, Gideon; Orrell, Catherine; Asiimwe, Stephen; Chimukangara, Benjamin; Giandhari, Jennifer; Pillay, Sureshnee; et al.
Background: Relationships between distinct antiretroviral therapy (ART) adherence patterns and risk of drug resistance are not well understood. Methods: We conducted a nested case–control analysis within a longitudinal cohort study of individuals initiating efavirenz-based ART. Primary outcomes of interest, measured at 6 and 12 months after treatment initiation, were: 1) virologic suppression, 2) virologic failure with resistance, and 3) virologic failure without resistance. Our primary exposure of interest was ART adherence, measured over the 6 months before each visit with electronic pill monitors, and categorized in three ways: 1) 6 months average adherence; 2) running adherence, defined as the proportion of days with average adherence over9 days of less than or equal to 10%, 20%, and 30%; and 3) number of 3-, 7-, and 28-day treatment gaps in the prior 6 months Results: We analyzed data from 166 individuals (107 had virologic failure during observation and 59 had virologic suppression at 6 and 12 months). Average adherence was higher among those with virologic suppression (median 83%, IQR 58–96%) versus those with virologic failure with resistance (median 35%, IQR 20–77%, pairwise P < 0.01) and those with virologic failure without resistance (median 21%, IQR 2–54%, pairwise P < 0.01). Although treatment gaps generally predicted virologic failure ( P < 0.01), they did not differentiate failure with and without drug resistance ( P > 0.6). Conclusions: Average adherence patterns, but not the assessed frequency of treatment gaps, differentiated failure with versus without drug resistance among individuals initiating efavirenz-based ART. Future work should explore adherence-resistance relationships for integrase inhibitor-based regimens.